Iron deficiency anemia in breastfeeding women and its impact to offspring’s health - Widodo, Ariani Dewi (World Nutrition Journal, 2024)
Breastmilk contains all the important nutrients for infant. The World Health Organization (WHO) recommends exclusive breastfeeding for infants up to six months of age to achieve optimal growth, development, and health. Breastfeeding also protects against illnesses such as diarrhea, pneumonia, and allergy. However not all women have similar condition, some health problems in breastfeeding mothers can affect the offspring such as anemia.